3-Phase Matheuristic Model in Two-Dimensional Cutting Stock Problem of Triangular Shape Items - Putra Bahtera Jaya Bangun; Sisca Octarina; Sisca Puspita Sepriliani; Laila Hanum; Endro Sastro cahyono (Science and Technology Indonesia, 2020)
Cutting Stock Problem (CSP) is a problem of cutting stocks with certain cutting rules. This study used the data of rectangular stocks, which cut into triangular shape items with various order sizes. The Modified Branch and Bound Algorithm (MBBA) was used to determine the optimum cutting pattern then formulated it into the 3-Phase Matheuristic model which consisted of constructive phase, improvement phase, and compaction phase. Based on the results, it showed that the MBBA produces three optimum cutting patterns, which was used six times, eight times, and four times respectively to fulfill the consumer demand. Then the cutting patterns were formulated into the 3-Phase Matheuristic model whereas the optimum solution was the minimum trim loss for the first, second and third patterns.